Dampened regulates the activating potency of Bicoid and the embryonic patterning outcome in Drosophila. - Liu, J.; Ma, J. (Nature communications, 2013)
The Drosophila morphogen gradient of Bicoid (Bcd) initiates anterior-posterior (AP) patterning; however, it is poorly understood how its ability to activate a target gene may have an impact on this process. Here we report an F-box protein, Dampened (Dmpd) as a nuclear cofactor of Bcd that can enhance its activating potency. We establish a quantitative platform to specifically investigate two parameters of a Bcd target gene response, expression amplitude and boundary position. We show that embryos lacking Dmpd have a reduced amplitude of Bcd-activated hunchback (hb) expression at a critical time of development. This is because of a reduced Bcd-dependent transcribing probability. This defect is faithfully propagated further downstream of the AP-patterning network to alter the spatial characteristics of even-skipped (eve) stripes. Thus, unlike another Bcd-interacting F-box protein Fate-shifted (Fsd), which controls AP patterning through regulating the Bcd gradient profile, Dmpd achieves its patterning role through regulating the activating potency of Bcd.